Execution time, kinetics, and kinematics of the mae-geri kick: Comparison of national and international standard karate athletes - Pozo, J.; Bastien, G.; Dierick, F. (Journal of Sports Sciences, 2011)
Little is known of the performance characteristics of the shotokan karate mae-geri kick. The aim of this study was to compare the execution time, the lower limb kinetics and kinematics, and their respective repeatability in the mae-geri kick of karate athletes of two different standards. Seventeen adult black belt karate competitors (9 national and 8 international athletes) performed six kicks with their dominant lower limb on a striking surface, combining maximum force impact and velocity. Execution time of movement and lower limb kinematics were recorded with a high-speed camera. Maximum force at impact and the forces exerted on the ground were measured using three force plates. The duration of the kick was significantly shorter for international than for national standard athletes. However, no significant difference in the maximum impact force of the kick was observed between the two groups. In addition, significant kinematic differences were observed between the groups, with two angles of motion and one velocity peak occurring sooner in the kick movement for the international athletes, specifically for the knee joint. International athletes also performed the kick with a significantly higher repeatability for duration and kinematics, specifically during the pre-loading phase that precedes the attack phase. We conclude that theduration of the kick and repeatability of lower limb kinematics could be useful in selecting top-level karate athletes and monitoring their training status.